2017
DOI: 10.1063/1.4990950
|View full text |Cite
|
Sign up to set email alerts
|

Local segregation versus irradiation effects in high-entropy alloys: Steady-state conditions in a driven system

Abstract: We study order transitions and defect formation in a model high-entropy alloy (CuNiCoFe) under ion irradiation by means of molecular dynamics simulations. Using a hybrid Monte-Carlo/molecular dynamics scheme a model alloy is generated which is thermodynamically stabilized by configurational entropy at elevated temperatures, but partly decomposes at lower temperatures by copper precipation. Both the high-entropy and the multiphase sample are then subjected to simulated particle irradiation. The damage accumulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 64 publications
4
23
0
1
Order By: Relevance
“…These results reveal that the short-range order maintains even under irradiation and the thermodynamically stabilised HEAs predicted in this study represent a steady-state configuration in a driven system. 98 To correlate the experimental observation of Cr/V segregation with the properties of irradiation-created defects, a rate theory model in which the defect mobilities and their recombination probability should be taken into consideration, is currently developing to investigate the steady-state conditions of the long-term microstructural evolution of the HEAs under irradiation. A further systematic investigation of point defect (vacancy and interstitial) properties would be very desirable for understanding the micro-structural evolution and the origin of exceptional radiation resistance in W-based HEAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results reveal that the short-range order maintains even under irradiation and the thermodynamically stabilised HEAs predicted in this study represent a steady-state configuration in a driven system. 98 To correlate the experimental observation of Cr/V segregation with the properties of irradiation-created defects, a rate theory model in which the defect mobilities and their recombination probability should be taken into consideration, is currently developing to investigate the steady-state conditions of the long-term microstructural evolution of the HEAs under irradiation. A further systematic investigation of point defect (vacancy and interstitial) properties would be very desirable for understanding the micro-structural evolution and the origin of exceptional radiation resistance in W-based HEAs.…”
Section: Resultsmentioning
confidence: 99%
“…43 A recent computational study on relationship between the SRO-induced local segregation and radiation effects in CoCuFeNi HEAs has been reported. 98 By using hybrid molecular dynamic and Monte-Carlo simulations, the study in question showed that the mobility of point defects created by irradiation can be changed and the system reaches a steady-state configuration of defect creation and annihilation with a tendency of copper segregation. For understanding of origin of the exceptional radiation resistance of the W-based HEAs under irradiation, a deeper investigation of kinetic properties of point defect migration and diffusion is crucial for clarifying additional mechanism for Cr and V segregation.…”
Section: (Crv)-mentioning
confidence: 99%
“…Therefore, various atomistic simulation techniques have been conducted to estimate the residual defects evolution. For example, the evolution of residual defects was analyzed using hybrid MC/MD simulations through a multiple cascade 25 and a kinetic Monte-Carlo (KMC) or MD simulation on a sample with point defects 15 , 26 . In this study, we chose the defect evolution simulation method which performs the MD simulation at a specific temperature on a sample containing randomly-distributed point defects in order to most efficiently analyze the interaction among residual defects given as point defects at a specific temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Can the high-dose limit be explored by a direct atomistic simulation? Studies involving applications of molecular dynamics to modeling high entropy alloys, exposed to a relatively high irradiation dose, were carried out by Koch et al [53] and Granberg et al [30]. The simulations, involving random initiations of many hundreds of cascade events in the same simulation cell, have enabled reaching the level of exposure close to φ ∼ 0.7.…”
Section: Introductionmentioning
confidence: 99%